2018
DOI: 10.1101/297085
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of stimulus polarity on detection thresholds in cochlear implant users: relationships with average threshold, gap detection, and rate discrimination

Abstract: Previous psychophysical and modelling studies suggest that cathodic stimulation by a cochlear implant (CI) may preferentially activate the peripheral processes of the auditory nerve, whereas anodic stimulation may preferentially activate the central axons. Because neural degeneration typically starts with loss of the peripheral processes, lower thresholds for cathodic than for anodic stimulation may indicate good local neural survival. We measured thresholds for 99-pulse-per-second trains of triphasic (TP) pul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 43 publications
1
9
1
Order By: Relevance
“…Moreover, similar observations in clinical studies demonstrated that the polarity sensitivity of ANFs is a potential approach to identify neural health in CI users to improve CI performance and enhance speech perception (Macherey et al, 2008;Van Wieringen et al, 2008;Undurraga et al, 2010;Carlyon et al, 2013Carlyon et al, , 2018Pfingst et al, 2015a,b;DeVries et al, 2016;Schvartz-Leyzac and Pfingst, 2018;Goehring et al, 2019;Jahn and Arenberg, 2019a;Mesnildrey et al, 2020). On the other hand, several studies on human CI recipients reported different and contradictory outcomes by using polarity sensitivity (Macherey et al, 2006(Macherey et al, , 2017Bahmer and Baumann, 2013;Karg et al, 2013;Undurraga et al, 2013;Hughes et al, 2017Hughes et al, , 2018Mesnildrey et al, 2017;Luo J. et al, 2020;Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…Moreover, similar observations in clinical studies demonstrated that the polarity sensitivity of ANFs is a potential approach to identify neural health in CI users to improve CI performance and enhance speech perception (Macherey et al, 2008;Van Wieringen et al, 2008;Undurraga et al, 2010;Carlyon et al, 2013Carlyon et al, , 2018Pfingst et al, 2015a,b;DeVries et al, 2016;Schvartz-Leyzac and Pfingst, 2018;Goehring et al, 2019;Jahn and Arenberg, 2019a;Mesnildrey et al, 2020). On the other hand, several studies on human CI recipients reported different and contradictory outcomes by using polarity sensitivity (Macherey et al, 2006(Macherey et al, , 2017Bahmer and Baumann, 2013;Karg et al, 2013;Undurraga et al, 2013;Hughes et al, 2017Hughes et al, , 2018Mesnildrey et al, 2017;Luo J. et al, 2020;Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 87%
“…Despite using triphasic pulse, Carlyon et al (2018) and Jahn and Arenberg (2019a) reported that up to 70% of investigated electrodes showed anodic sensitivity and could not prove polarity behavior as an indicator for estimating neural survival. Similar to their results, we found more anodic sensitivity using asymmetric pulses, such as pseudomonophasic and triphasic pulses, in the perimodiolar array.…”
Section: Effect Of Pulse Shapementioning
confidence: 96%
See 3 more Smart Citations